2014
DOI: 10.1111/gwmr.12070
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Field Screening Method Based on Bubbling Extraction and Photoionization Detection for Measurement of Benzene and Total VOCs

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.2008), high-resolution site characterization (USEPA 2013) among other initiatives; as ways of streamlining site assessment activities. The triad approach involves three elements: systematic project planning, dynamic work plan strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Inspired by the naturally occurring selective enrichment of organic matter in bursting greenhouse gas microbubbles, numerous bubbling extraction systems have been developed to remove organic pollutants and natural products by using oxygen, hydrogen, ambient air, nitrogen, and other gases bubbling through liquid samples. Fizzy extraction was recently developed to monitor the released medium-polarity volatile and semivolatile compounds dissolved in liquid matrices with CO 2 carrier gas. An effervescent tablet-induced extraction can facilitate the extraction of volatiles dissolved in liquid matrices . Preconcentration of organic solutes in urine was achieved based on the collection of induced bursting bubble aerosols .…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the naturally occurring selective enrichment of organic matter in bursting greenhouse gas microbubbles, numerous bubbling extraction systems have been developed to remove organic pollutants and natural products by using oxygen, hydrogen, ambient air, nitrogen, and other gases bubbling through liquid samples. Fizzy extraction was recently developed to monitor the released medium-polarity volatile and semivolatile compounds dissolved in liquid matrices with CO 2 carrier gas. An effervescent tablet-induced extraction can facilitate the extraction of volatiles dissolved in liquid matrices . Preconcentration of organic solutes in urine was achieved based on the collection of induced bursting bubble aerosols .…”
Section: Introductionmentioning
confidence: 99%
“…Li (2007) indicated that the drop in correlation is caused by the increase in water content and volatile solids in soil samples. Devine et al (2014) also suggested that high humidity tends to decrease the detector response of PID because the water vapour can absorb and diffuse the light that is trying to ionise the compounds. The low test kit on-site readings may also be engendered by the inappropriate settings of the turbidity meter.…”
Section: Possible Causes Influencing the Regression Resultsmentioning
confidence: 99%
“…The PID lamp absorbed the chemicals emitted and then ionized the chemical to provide an ionization response, which was then displayed as the concentration of the chemical as "ppm" (parts per million). The PID had an internal sampling draw pump that was calibrated using a standard reference gas, Isobutylene gas, and can also be calibrated using by two-point field zero [15,16]. Charged particles migrated to the electric field towards the respective electrodes, generating a current that was indicative of the number of formed ions + electron pairs, regardless of the compounds present in the chamber [17].…”
Section: Btex Monitoring Using Pidmentioning
confidence: 99%